2012
DOI: 10.1016/j.nima.2012.04.090
|View full text |Cite
|
Sign up to set email alerts
|

Control strategies for the final focus of future linear particle collider

Abstract: a b s t r a c tThis paper presents a simple model of the final focus of a linear particle collider. Adopting an integrated approach, several control strategies are tested to stabilize the mechanical parts, and control the beam. One of the key features of the model is that it has been updated using vibration spectra measured in the CMS experimental area of the LHC. Using this model, it has been possible to estimate objectively the performances of a final focus system, compare and propose new solutions to improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Contribution of mechanical jitter to overall vibration budget (right) additional mechanical jitter, coming from, for example, vibrations induced by the liquefier or flow of liquid helium. A modelling program to ensure that the ground to magnet transfer function is correct is ongoing [159].…”
Section: Feedback and Bpmsmentioning
confidence: 99%
“…Contribution of mechanical jitter to overall vibration budget (right) additional mechanical jitter, coming from, for example, vibrations induced by the liquefier or flow of liquid helium. A modelling program to ensure that the ground to magnet transfer function is correct is ongoing [159].…”
Section: Feedback and Bpmsmentioning
confidence: 99%
“…During the last twenty years, many studies have been conducted in order to comply with these requirements, both for the active stabilisation of the main beam quadrupoles [6][7][8], and for the stabilisation of final focus quadrupoles [9][10][11][12][13][14][15]. A critical review of strategies can be found in [16]. Over the years, the level of stability has been continuously improved, reaching the required values and even better.…”
Section: Introductionmentioning
confidence: 99%
“…Figure16. Experimental transfer function between the inertial sensor on the structure and the Guralp on the table without (red) and with control (green).…”
mentioning
confidence: 99%
“…For the CLIC [5][6][7] beam structure intratrain feedback is less efficient and a combination of a careful design of the support structures with an active stabilization system is required [8][9][10], in combination with a repositioning system [11] and a preisolator [12]. The CLIC final doublet is required to be as stable as 0.15 nm above 4 Hz [5].…”
Section: Introductionmentioning
confidence: 99%